The Problems in English Learning Speaking Class VII by Students Satu Atap Sukun Junior High School in Academic Year 2024-2025 - Yanto Yanto; Mas Buyung; Nur Syamsiyah Ekhsan (International Journal of Education and Literature, 2025)
This study aims to identify various problems faced by students class VII at junior high school Satu Atap Sukun in learning to speak English, as well as the role of teacher in overcoming these challenges, specifically with seventh-grade students. The researcher is interested in exploring the issues faced at junior high school Satu Atap Sukun and the strategies implemented by teacher to help students overcome these difficulties. The research method used is qualitative, with data collection techniques through interviews and observations. The results found in this study indicate that the researcher identified problems in learning English speaking skills among students class VII at Junior High School Satu Atap Sukun, as well as the teacher strategies to solve these problems. The problems experienced by the students class VII at Junior High School Satu Atap Sukun are as follows: no experience in English learning from the basics, lack of motivation to English learning, lack of self-confidence, limited English vocabulary, very limited time for English learning, lack of learning facilities and teaching media, no English speaking practice outside of school, and the influence of an environment that uses the mother tongue. Meanwhile, the teacher strategies to overcome the English speaking problems among students class VII at Junior High School Satu Atap Sukun include group discussion strategy, role-play strategy, and whisper relay strategy.